Economic valuation approach to calculating pollution loads in Kenjeran area, East Java, Indonesia - Mauludiyah (Journal of Marine Resources and Coastal Management, 2022)
Environmental pollution is not a new problem in the Kenjeran, Surabaya coastal area. There are numerous studies show that these waters have been polluted. However, there is no specific study on the economic valuation of environmental impacts due to pollution that occurs in the area. The purpose of this study was to estimate the costs incurred from pollution that occurred in the Kenjeran coastal area. The estimation of the cost of pollution is done by calculating the decrease in fishery productivity and the tourism sector, and the increase in health and water treatment costs. Data collection techniques were carried out through secondary data collection, interviews, questionnaires, field surveys, and focused group discussions. The calculation results show that the costs incurred from pollution that occur in the coastal area of Kenjeran are Rp. 452,724,903,588,63 include (1) a decrease in fishery productivity in the form of lost fisherman income of Rp. 28,728,000,000.00; (2) a decrease in the tourism sector by Rp. 27,728,112,300.00; (3) the increase in health costs includes the cost of carcinogenic risk of Rp. 363,626,479,099.79 and gastroenteritis of Rp. 32,552,893,425.42; and (4) an increase in the cost of water treatment by Rp. 89,418,763.42. This effort is needed to remind policy makers of the importance of paying attention to the impacts arising from an activity on the environment and society as well as to show that environmental aspects are an important potential for long-term sustainable development activities and not as an obstacle to development.